Practicing "unsettled listening" to the migration narratives of young adolescent refugees. Issue 4 (8th August 2019) - Reyes, Cynthia C.
Abstract: Forced migration generally refers to groups of people who are displaced by conflicts related to natural or environmental disasters, or war. This conceptual article takes up the topic of teaching children who have experienced forced migration due to war from ethnic or religious conflict, and the stories of trauma they may bring into a classroom. Through a middle grades classroom vignette, this piece proposes a framework for using cultural humility and a multidimensional lens for understanding the trauma that refugee children may experience prior to, during, and post-migration. This type of unsettled listening and orientation to migration is a first step to enhancing interactions between students and their teachers that may lead to impactful and lasting positive schooling experiences.